2018
DOI: 10.1002/jcb.26887
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C activator bryostatin‐1 modulates proteasome function

Abstract: Proteasome activity in ubiquitin-proteasome pathway plays a pivotal role in degradation and clearance of aggregated, oxidized, damaged, and misfolded unwanted proteins to control protein homeostasis or proteostasis. Proteasome activity decreases with cellular senescence, aging, and age-related diseases. Therefore, enhancement of impaired proteasome function by molecular biological and/or pharmacological intervention is an active area of research. Bryostatin-1, a naturally occurring macrocyclic lactone, activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…hours to reach maximum effect both for HDACi and PKCa, suggesting a transcriptional effect either on the expression of the antigen processing machinery or on proteins regulating its activity rather than a direct binding to peptidases' catalytic sites. Bryostatin can enhance proteasome activities in fibroblasts [43] while disulfiram effect on NF-κB inhibited proteasome activities in cell lines [42]. The RNA expression of some proteasome subunits was modulated in an in vitro latency model upon LRA treatment [55] but neither proteasome expression and hydrolytic activities, nor the impact on antigen processing were assessed.…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…hours to reach maximum effect both for HDACi and PKCa, suggesting a transcriptional effect either on the expression of the antigen processing machinery or on proteins regulating its activity rather than a direct binding to peptidases' catalytic sites. Bryostatin can enhance proteasome activities in fibroblasts [43] while disulfiram effect on NF-κB inhibited proteasome activities in cell lines [42]. The RNA expression of some proteasome subunits was modulated in an in vitro latency model upon LRA treatment [55] but neither proteasome expression and hydrolytic activities, nor the impact on antigen processing were assessed.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Peptides displayed by MHC-I to CD8 T or NK cells derive from the intracellular degradation of proteins by the antigen processing machinery, including proteasomes and post-proteasomal peptidases in the cytosol and endoplasmic reticulum (ER) where LRA-induced HIV antigens may be found [31]. The expression and hydrolytic activities of the antigen processing machineries are modulated by various stimuli such as cytokines [32], viral infection [33], TLR ligands [34][35][36], TCR-induced cellular activation [37], oxidative stress [38] or enzyme inhibitors [39][40][41][42][43]. We previously showed that TCR-mediated cellular activation enhanced peptidase activities, modulated protein degradation patterns into peptides and CTL recognition [37].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the work of Khan et al work demonstrated that bryo 1 could increasep roteasome function through PKC modulation in cells. [43] 2.6 Challenges related to the biological activity of bryostatin 1…”
Section: Bioactivitiesofb Ryostatin 1i Ncentral Nervous System Diseasesmentioning
confidence: 99%
“…The actual procedure of measurement of proteasome activity using fluorometric assay has been published elsewhere (Khan and Nelson, 2018). In principle, the assay monitored the chymotrypsin-like activity of the 20S proteasome assembly using a 7-amino-4-methylcoumarin (AMC)-tagged peptide substrate (Succ-LLVY-AMC) (BioVision (Milpitus, CA).…”
Section: Measurement Of Proteasome Activity Using Fluorometric Assaymentioning
confidence: 99%
“…The procedure of standardization of the proteasome activity assay has been published elsewhere (Khan and Nelson, 2018). Briefly, standardizing reagent, we used a positive control sample (Jurkat Cell lysate; BioVision, Milpitas, CA) with significant proteasome activity for standardization of the fluorescence spectrometer.…”
Section: Measurement Of Proteasome Activity Using Fluorometric Assaymentioning
confidence: 99%